A Collection of Original Papers Relative to The History of the Colony of Massachusetts-Bay 492 (1769) - (:unkn) unknown (My University, 1769)
Prohibited the selling or bartering guns, ammunition, and swords to "any Indian," punishable by fine.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES